Application of the Principle of Appropriateness in a Peer to Peer Lending Contract - Debora Debora; Haposan Siallagan; Michelle Lukcy Magdelene (Institute Of computer Science (IOCS), 2023)
In implementing P2PL, an agreement is an important tool that binds the legal relations of the parties and evidence of the existence of a transaction. The contents of an agreement cannot be separated from the Appropriateness principle. The P2PL organizer is not responsible for the risk of default. Failure to fulfill the principle of decency in the P2PL agreement results in no justice being realized, because certain parties are harmed. This study discusses the standard contracts in P2PL agreements and the application of the principle of appropriateness in P2PL agreements as an effort to fulfill justice. Based on the research results, the type of contract used in P2PL is a standard contract which tends to show an imbalance in the rights and obligations of the parties. The benchmark for the principle of Appropriateness contained in Article 1339 of the Civil Code can be determined from a sense of justice. Adequacy requirements originate from laws and regulations which can be realized by balancing the positions of the parties. In forming laws and regulations, it must be able to accommodate the interests of all parties. If there is a dispute related to the implementation of the agreement, the law enforcer must Appropriateness principle of justice compared to agreements made on the basis of mere freedom of contract. P2PL organizers without collateral clearly do not provide good protection to lenders. The consequence of the unsecured loan system is high interest rates. Billing mechanisms often result in defamation.